PROFESSIONAL EDUCATION OF EDUCATIONAL LEADERS: THE EXPERIENCE OF UTRECHT UNIVERSITY (THE NETHERLANDS) - Iryna Reheilo; Mariia Saiuk (Неперервна професійна освіта: теорія та практика)
The problem of developing managerial leadership potential for higher education, which acts as a direct catalyst for the organization of quality educational services in Ukraine and increasing the competitiveness of national higher education institutions, remains a priority at the stage of Ukraine's integration into the European Union. The article first examines the issue of professional training of educational leaders and managers in the field of higher education on the example of Utrecht University (the Kingdom of the Netherlands). Taking into account the review of previous studies carried out in the national space, as well as the study of relevant continental European sources, the data on the Dutch higher education system are updated. Based on the analysis of specialized legislation in the field of higher education and relevant institutional acts, the approaches to master's training in the Netherlands are characterized, the key among which is interdisciplinary. It is found that master's programmes are offered at research universities and universities of applied sciences; their duration varies from 1 to 4 years and ranges from 60 to 240 ECTS credits. It has been found that the undisputed trend in master's training is the uniqueness of educational programmes that correspond to the mission and vision of universities. It is established that among the offers on the market of educational services that further offer professional activities in the field of higher education management, there are master's degree programmes in pedagogy, management, art, administration and management, sociology, psychology, etc. The profiles of educational programmes of the University of Utrecht, in particular, specialties with a diverse academic load, which offer graduates after successful graduation positions in the Government of the Netherlands, sectors dealing with education, the Dutch Education Inspectorate, non-governmental educational organizations, as developers and reformers of educational policies, are considered.